Incidence of Mutation and Deletion in Topoisomerase IIα mRNA of Etoposide and mAMSA–resistant Cell Lines - Matsumoto, Yoshihito (Jpn J Cancer Res, 2001)
The efficacy of all chemotherapeutic agents is limited by the occurrence of drug resistance. To further understand resistance to topoisomerase II inhibitors, 50 sublines were isolated as single clones from parental cells by exposure to VP–16 (etoposide) or mAMSA (m–amsacrine). Subsequently, a population of cells from each subline was exposed to three–fold higher drug concentrations allowing 16 stable sublines to be established at higher extracellular drug concentration. Finally, 66 sublines were picked up. The frequency and nature of mutations in the topoisomerase II gene in the drug–selected cell lines were evaluated. In order to screen a large number of cell lines, an RNAse protection assay was developed and mismatches were observed in 13.6% of resistant cell lines (12% of resistant cell lines exposed to lower drug concentrations and 18.8% of resistant cell lines exposed to higher drug concentrations). Some of these mutations are located in vital regions of topoisomerase II (phosphorylation sites in the C–terminal or N–terminal, and nuclear localizing signal of topoisomerase II). Our findings suggest that mutations of topoisomerase II gene are an important and frequent mechanism of resistance to topoisomerase II inhibitors.